A fighting chance - Meléndez Salinas, Claudia (Piñata Books, Arte Público Press, 2015)
Seventeen-year-old Miguel Ángel is an aspiring boxer who avoids gang violence by working out every day with the Alisal Boxing Club. Can he avoid succumbing to the gangbangers in his neighborhood and have a successful relationship with his beautiful girlfriend Britney? Can their love survive all of the conflict in their lives?